The Donkey rodeos: A current model of territorial commonality in the Quebrada de Humahuaca, Jujuy, Argentina - Cladera, Jorge Luis (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
Through the analysis of first-hand ethnographic material and its discussion with certain documentary sources and with contemporary historiographic advances, we study a practice of collective work that is still in force in the 21st century among the rural communities of Puna and Quebrada regions, in the province of Jujuy: the rodeos de burros (donkey rodeos). Three aspects of this practice are addressed: firstly, the conceptual and symbolic specificities that asinine cattle acquire in the local ontological system. Secondly, the system of collective work organization that is displayed in the activity of rodeos, thus identifying two different mechanisms of social cooperation and territorial coordination in contemporary practices. Finally, the mutual enchainments of these practices, thus producing different chains of supra-community regional identity. Through the approach of two documentary sources from the 19th century, we study how these three characteristics acquired their current form as a mechanism for the reordering of collective identities and territories in the context of the ethnic and juridical de-structuring suffered by the indocolonial communities in the face of the advances of the liberal state system.